Always and forever - Durant, Alan, 1958-; Gliori, Debi (Orlando : Harcourt, 2004)
A family of forest animals learns to cope with the death of a loved one.
Keywords: Death -- Fiction; Grief -- Fiction; Forest animals -- Fiction